ETHNOCENTRISM AND ANIMOSITY IN CONSUMER BEHAVIOR IN BOSNIA AND HERZEGOVINA AND IMPLICATIONS FOR COMPANIES - Nenad Brkić; Miralem Čorbo; Denis Berberović (Economic Review)
This study attempts to examine ethnocentrism of BiH consumers, animosity tendencies, and consumers' notions of products originating from two neighboring countries – Croatia and Slovenia. The aim is to expose the causal relation between the expression of an individual's animosity, her/his understanding of neighboring countries' image, and her/his degree of ethnocentrism. Klein, Ettenson and Morris (1998) argued that animosity (one of COI – Country of Origin Image aspects) affects consumer behavior, but not the assessment of products originating from this country. This study seeks to examine this argument. The regression analysis confirmed this assumption on a sample of 300 BiH consumers. Additionally one marketing scale and one psychological scale were used: one for measuring consumer ethnocentrism, and the other for measuring country of origin image. This study used the method of mall intercepts – intercepting customers in large shopping malls. Data was processed using ACNOVA, Cronbach alpha and hierarchical regression analysis.